Association of Genetic Variability in Selected Genes in Patients With Deep Vein Thrombosis and Platelet Hyperaggregability. (October 2018) - Sokol, Juraj; Skerenova, Maria; Ivankova, Jela; Simurda, Tomas; Stasko, Jan
The aim of this study was to evaluate the genetic variability of the selected single nucleotide polymorphisms (SNPs) and examine the association between these SNPs and risk for deep vein thrombosis (DVT) in patients with sticky platelet syndrome (SPS). We examined 84 patients with SPS and history of DVT and 101 healthy individuals. We were interested in 2 SNPs within platelet endothelial aggregation receptor 1 (PEAR1) gene (rs12041331 and rs12566888), 2 SNPs within mkurine retrovirus integration site 1 gene (rs7940646 and rs1874445), 1 SNP within Janus kinase 2 gene (rs2230722), 1 SNP within FCER1G gene (rs3557), 1 SNP within pro-platelet basic protein (rs442155), 4 SNPs within alpha2A adrenergic receptor 2A (ADRA2A; rs1800545, rs4311994, rs11195419, and rs553668), and 1 SNP within sonic hedgehog gene (rs2363910). We identified 2 protective SNPs within PEAR1 gene and 1 risk SNP within ADRA2A gene (PEAR1: rs12041331 and rs12566888; ADRA2A: rs1800545). A haplotype analysis of 4 SNPs within ADRA2A gene identified a risk haplotype aagc ( P = .003). Moreover, we identified 1 protective haplotype within PEAR1 gene (AT, P = .004). Our results support the idea that genetic variability of PEAR1 and ADRA2A genes is associated with platelet hyperaggregability manifested as venous thromboembolism. The study also suggests a possible polygenic type of SPS heredity.